2000
DOI: 10.1177/00139160021972450
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of the Antarctic Winter on Indian Expeditioners

Abstract: The authors studied the psychological variables of 25 men who participated in the winter-over team of an Indian expedition to Antarctica for possible associations with seasonality and isolation. It was found that increased cigarette smoking was associated with the stress of the beginning of isolation (March), sleep difficulty was associated with midwinter (June), rapport was at a minimum at the point of maximum isolation in temporal terms (September), and decreased satisfaction with work and life situations wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 25 publications
4
34
2
Order By: Relevance
“…The alterations in lightdark periodicity in polar regions disrupt the circadian sleep cycle, resulting in considerable sleep disturbances during the darkness period, and an associated decline in subjective feelings of well-being and alertness in polar areas (Bhargava et al 2000;Natani et al 1970;Palinkas et al 1995a;Palinkas et al 1996). Also in space, the loss of the 24-h light/dark cycle, circadian disruption, microgravity, and workload demands may result in performance decrements, decreased alertness and sleep disruptions (Mallis and Deroshia 2005).…”
Section: Psychological Functioningmentioning
confidence: 99%
See 2 more Smart Citations
“…The alterations in lightdark periodicity in polar regions disrupt the circadian sleep cycle, resulting in considerable sleep disturbances during the darkness period, and an associated decline in subjective feelings of well-being and alertness in polar areas (Bhargava et al 2000;Natani et al 1970;Palinkas et al 1995a;Palinkas et al 1996). Also in space, the loss of the 24-h light/dark cycle, circadian disruption, microgravity, and workload demands may result in performance decrements, decreased alertness and sleep disruptions (Mallis and Deroshia 2005).…”
Section: Psychological Functioningmentioning
confidence: 99%
“…Other psychological stress reactions have also been reported. During the long winter-over period in Antarctica, personnel have reported increases in depressive mood, psychosomatic complaints, and interpersonal conflicts, and a decrement in work performance (Bhargava et al 2000;Ikegawa et al 1998;Palinkas et al 1995aPalinkas et al , b, 1996Palinkas and Johnson 1990). Likewise anecdotal and behavioral evidence from space missions show that crewmembers have experienced psychological reactions that have included lapses of attention, emotional liability, psychosomatic symptoms, irritability toward crewmates and/or mission control staff, and a considerable decline in vigor and motivation (Kanas and Manzey 2003;Suedfeld 2005).…”
Section: Psychological Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Using questionnaire methods, Bhargava et al (2000) reported that wintering members of the Indian Antarctic Expedition suffered from sleep disturbances and other behavioural adjustments during midwinter months. In view of the evidence from previous sleep studies carried out in the Antarctic, and subjective reports of sleep disturbances in the Indian station, the present study was undertaken with the aim of using polysomnographic techniques to objectively evaluate the sleep pattern of six wintering members of the 24th Indian Antarctic Expedition with respect to their prolonged stay in the harsh Antarctic environment.…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocial features may perform a significant role in the individual adaptation to extreme environments (Bhargava, Mukerji & Sachdeva, 2000;Johnson, Boster & Palinkas, 2003). Research has revealed the key roles leadership and gender differences play in the functioning of the group and both factors are acknowledged as cohesion and adjustment facilitators within the team.…”
Section: Discussionmentioning
confidence: 99%